PENGARUH AROMATERAPI LAVENDER TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI ELEKTIF DI RUANG PERAWATAN BEDAH CHARITAS HOSPITAL KM 7 PALEMBANG - Nopriani, Yora; Refitania , Venny; Firdaus, Nuzula (Jurnal Kesehatan dan Pembangunan, 2025)
Preoperative action is a stressor for patients that can evoke a stress reaction both physiologically and psychologically. Anxiety is one of them. One of the efforts to overcome anxiety levels is the use of lavender aromatherapy. Objective: This study aims to determine the effect of lavender aromatherapy on the anxiety level of elective preoperative patients.Methods: The study used the Pre Experiment design method with a one group pre post test design, with a sample of 35 respondents. Sampling was carried out by purposive sampling technique. Data analysis using univariates, bivariates (Wilcoxon Test) Results: The results of the study obtained a significant value of the non-parametric statistical test (Wilcoxon) sign rank was <0.001 (p value < 0.05) which means that there is an effect of lavender aromatherapy on the anxiety level of elective preoperative patients. It is hoped that the results of this study can be used as reference materials and become one of the options for non-pharmacological therapy for anxiety management.